Penerapan Kedisiplinan Saat Makan pada Anak Usia 5 – 6 Tahun dengan Metode Foto Bercerita - Henderia Kustina; Erhamwilda (UNISBA Press, 2021)
Abstract. The purpose of this study was to see the impact of the using the photo storytelling method on increasing the discipline of children aged 5-6 years while eating according to the eating etiquette in Islam. This research departs from the fact that there are still children aged 4-6 years who have not followed eating etiquette, including: not being able to wash their hands before eating, eating while sitting, forgetting to pray before eating, chatting while eating, not holding a spoon properly, not being used to using the right hand when eating, and not tidying up eating utensils. This research is a qualitative research with case study method, the subjects of this research are children aged 5-6 years in one of the villages in the District Rancasari Bandung. The cases studied were 3 (three) children and the data collection techniques were through interviews and observations as well as documentation studies. The results showed an increase in the ability to discipline when eating with the photo storytelling method in the children aged 5-6 years studied. After using the storytelling photo method, the child successfully applies eating etiquette including: washing hands before eating, eating while sitting, praying before eating, not talking when eating, holding a spoon properly, using the right hand when eating, and tidying up eating utensils in daily activities. Abstrak. Tujuan penelitian ini adalah melihat dampak dari penggunaan metode foto bercerita pada peningkatan kedisiplinan anak usia 5 – 6 tahun saat makan sesuai etika makan dalam Islam Penelitian ini berangkat dari fakta masih adanya anak usia 4-6 tahun yang belum mengikuti etika makan antara lain: belum dapat mencuci tangan sebelum makan, makan sambil duduk, lupa berdoa sebelum makan, mengobrol ketika makan, belum memegang sendok dengan benar, belum terbiasa menggunakan tangan kanan ketika makan, dan belum membereskan peralatan makan. Penelitian yang dilakukan adalah penelitian kualitatif dengan metode studi kasus, subjek penelitian ini adalah anak-anak usia 5 – 6 tahun di salah satu Kelurahan di Kecamatan Rancasari Bandung. Kasus yang diteliti adalah 3 (tiga) anak dan teknik pengumpulan data melalui wawancara dan observasi serta studi dokumentasi. Hasil penelitian menunjukan adanya peningkatan kemampuan kedisiplinan saat makan dengan metode foto bercerita pada anak usia 5 – 6 tahun yang diteliti. Setelah menggunakan metode foto bercerita anak berhasil menerapkan etika makan meliputi: mencuci tangan sebelum makan, makan sambil duduk, berdoa sebelum makan, tidak mengobrol ketika makan, memegang sendok dengan benar, menggunakan tangan kanan ketika makan, dan membereskan peralatan makan dalam kegiatan sehari-hari.